Spatiotemporal trends of Type 2 diabetes due to low physical activity from 1990 to 2019 and forecasted prevalence in 2050: A Global Burden of Disease Study 2019 - Shujin Fan; Jin Xu; Jinli Wu; Li Yan; Meng Ren (Elsevier, 2024)
Background: Type 2 diabetes mellitus (T2DM) poses a major global health burden, yet epidemiological research on low physical activity's (LPA) impact is limited. This study examines LPA's global effect on T2DM. Methods: Analyzing Global Burden of Disease Database (GBD) 2019, we explored LPA-attributable T2DM deaths and Disability-Adjusted Life Years (DALYs) from 1990 to 2019, stratified by year, gender, country, and SDI regions. Estimated Annual Percentage Change (EAPC) assessed trends, and Bayesian models predicted future patterns. Results: In 2019, LPA accounted for a substantial 8.5% of T2DM deaths and 6.9% of DALYs, representing a noticeable rise since 1990. Age-standardized mortality rates (ASMR) and disability-adjusted life years rates (ASDR) increased globally, particularly in low Socio-Demographic Index (SDI) regions. High and high-middle SDI regions saw a decrease in ASMR, while all regions generally saw an upward trend in ASDR. Projections for 2050 suggest a declining ASMR but an increasing ASDR, indicating a continuing burden of T2DM despite potential mortality reductions. Conclusion: LPA significantly impacts T2DM, particularly in low SDI regions. Promotion of physical activity is crucial to reduce this burden, particularly in regions where the disease's impact is most severe.